Ravulizumab in NMOSD with associated interstitial pneumonitis in a 59-year-old female patient: a case report - Neundorf, Andrea; Dittrich, Ralf (Frontiers in Immunology, 2026)
IntroductionNeuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system often associated with aquaporin-4-immunoglobulin-G (AQP4-IgG), which activate the complement system, and it can lead to progressive neurological disability. Complement inhibitors have been shown to be effective in preventing relapses. While there exist rare case reports on the early initiation of eculizumab in the acute exacerbation phase, no data are available for early treatment with ravulizumab.CaseA 59-year-old patient was diagnosed with AQP4-IgG seropositive NMOSD upon presentation with paraplegia, and MRI-confirmed longitudinally extensive transverse myelitis from C2 to T5 in November 2023. Treatment included high-dose methylprednisolone, followed by immunoadsorption (IA) and complement-inhibition therapy with ravulizumab initiated 13 days after attack onset alongside with IA. The patient additionally developed an interstitial pneumonia complicating the case, likely attributable to complement-mediated autoimmune processes. Over time, there was significant improvement in neurological and respiratory conditions, as evidenced by reduced spinal cord edema and partial resolution of pulmonary infiltrates on follow-up imaging in January 2024. By January 2025, the patient exhibited further neurological improvement and regained the ability to stand upright with external support. Ravulizumab therapy was well tolerated, and the patient will continue with eight-weekly infusions.ConclusionOverall, this case highlights that early targeted immunotherapy with ravulizumab within two weeks of attack onset, supported by IA, can be an effective choice for controlling NMOSD disease activity and improving patient outcomes. NMOSD-related interstitial pneumonitis, though rare, underscores the need for vigilance in recognizing atypical manifestations of the disease.